Damped Vibrations of Hydraulic Cylinder with a Spring-damper System in Supports. (2017) - Sochacki, Wojciech; Bold, Marta
Abstract: The description of the damped vibrations of hydraulic cylinder has been presented in this paper. The dissipation of vibration energy was caused by different kinds of damping on vibrations of hydraulic cylinder. Damping in adopted model is a result, of taken into account internal damping of viscoelastic material of beams that modelled the system, external viscous damping and constructional damping of supports. In this paper, the problem of transverse and longitudinal damped vibration of hydraulic cylinder was formulated and solved. The influence on the damped vibration frequency and the degree of vibration amplitude decay of damping coefficient and spring rigidity coefficient were presented.